2009
DOI: 10.1155/2009/957602
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Maize Genomics and Their Value for Enhancing Genetic Gains from Breeding

Abstract: Maize is an important crop for food, feed, forage, and fuel across tropical and temperate areas of the world. Diversity studies at genetic, molecular, and functional levels have revealed that, tropical maize germplasm, landraces, and wild relatives harbor a significantly wider range of genetic variation. Among all types of markers, SNP markers are increasingly the marker-of-choice for all genomics applications in maize breeding. Genetic mapping has been developed through conventional linkage mapping and more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 262 publications
0
37
0
1
Order By: Relevance
“…Nevertheless, the success of this strategy is limited because of low genetic variations in the gene pools as a result of domestication, high costs and long generation times to produce a single improved selection (Xu et al 2009). Future demands require new and ameliorated high-yield cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the success of this strategy is limited because of low genetic variations in the gene pools as a result of domestication, high costs and long generation times to produce a single improved selection (Xu et al 2009). Future demands require new and ameliorated high-yield cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…1(A) (Liu et al, 2003;Flint-Garcia et al, 2005;Liu et al, 2008). NAM 집단에 사용된 대표적 인 교배친들로는 Suwan(태국계통), Ki3(한발 감수성), Ki11 (한발 저항성) 등이 교배친으로 이용되었으며, 또한 CIMMYT 에서 개발한 열대성 품종 8개(CML52, CML69, CML103, CML228, CML247, CML277, CML322, CML333) 등이 이 용되었다 을 얻을 수 있는 반면 (Messmer et al, 2009;Szalma et al, 2007) (Tuberosa et al, 2002b;Campos et al, 2004;Xu et al, 2009). (Xiao et al, 2005;Hao et al, 2008).…”
Section: Ngs(next-generation Sequencing)unclassified
“…other major problem is that in many of the previous drought qtl studies, there has been a tendency to examine crosses between lines that were not agronomically elite (landraces or exotic materials) and/or did not exhibit extreme differences in yield under stress. QTL are often germplasm-specific and the costs for applying MAS for many qtl of small effect may be greater than those of conventional cross-breeding (31).…”
Section: Qtl Mapping and Marker Assisted Selection (Mas)mentioning
confidence: 99%
“…In maize, however, QTL studies in the past have not identified any QTL with sufficiently large effects to be effectively used in MAS programs (31). Recently a conceptual framework for molecular breeding towards drought tolerance based on the Passioura equation of expressing yield as the product of water use (WU), water use efficiency (WUE) and harvest index (HI) was proposed (20).…”
Section: Qtl Mapping and Marker Assisted Selection (Mas)mentioning
confidence: 99%